Eye tracking and attentional bias for depressive internet memes in depression - Umair Akram; Jason G. Ellis; Glhenda Cau; Frayer Hershaw; Ashlieen Rajenthran; Mollie Lowe; Carissa Trommelen; Jennifer Drabble (Experimental Brain Research, 2021)
Previous research highlights the potential benefits of engaging with depressive internet memes for those experiencing symptoms of depression. This study aimed to determine whether: compared to non-depressed controls, individuals experiencing depressive symptoms were quicker to orient and maintain overall attention for internet memes depicting depressive content relative to neutral memes. N = 21 individuals were grouped based on the severity of reported depression symptoms using the PhQ-9. Specifically, a score of: ≤ 4 denoted the control group; and ≥ 15 the depressive symptoms group. Participants viewed a series of meme pairs depicting depressive and neutral memes for periods of 4000 ms. Data for the first fixation onset and duration, total fixation count and total fixation and gaze duration of eye-movements were recorded. A significant group x meme-type interaction indicated that participants with depressive symptoms displayed significantly more fixations on depressive rather than neutral memes. These outcomes provide suggestive evidence for the notion that depressive symptoms are associated with an attentional bias towards socio-emotionally salient stimuli.